Local government financial performance: the effects of capital expenditure and intergovernmental revenue (The case of South Sumatra Province, Indonesia) - Muhammad Husni Mubarok; Abdillah Arif Nasution; Sambas Ade Kesuma; Widyawati Pangestu (Jurnal Perspektif Pembiayaan dan Pembangunan Daerah, 2022)
The main purpose of this study is to examine the effects of capital expenditure and intergovernmental revenue on local government financial performance in South Sumatra Province, Indonesia. The result is expected to extend the knowledge about local government financial performance and different relevance of financial performance factors. Data on seventeen districts/cities in South Sumatra Province during 2014-2018 were used to test the research model. The data is sourced from the financial reports of the district/city government of South Sumatra province and the Central Statistics Agency. The analytical results showed that capital expenditure is statistically positive and has a significant effect on the financial performance of local governments. Meanwhile, the intergovernmental revenue is negative and significantly affects local government financial performance. Future studies should consider various variables that may influence the financial performance of local governments. Future studies could also use different methodologies such as focus groups and interviews.